Perspectives of nurses' role in interprofessional pharmaceutical care across 14 European countries: A qualitative study in pharmacists, physicians and nurses - De Baetselier, Elyne; Dilles, Tinne; Batalha, Luis M; Dijkstra, Nienke E; Fernandes, Maria I; Filov, Izabela; Friedrichs, Juliane; Grondahl, Vigdis A; Heczkova, Jana; Helgesen, Ann Karin; Jordan, Sue; Keeley, Sarah; et al. (PloS one, 2021)
OBJECTIVES: To understand healthcare professionals' experiences and perceptions of nurses' potential or ideal roles in pharmaceutical care (PC). DESIGN: Qualitative study conducted through semi-structured in-depth interviews. SETTING: Between December 2018 and October 2019, interviews were conducted with healthcare professionals of 14 European countries in four healthcare settings: hospitals, community care, mental health and long-term residential care. PARTICIPANTS: In each country, pharmacists, physicians and nurses in each of the four settings were interviewed. Participants were selected on the basis that they were key informants with broad knowledge and experience of PC. DATA COLLECTION AND ANALYSIS: All interviews were conducted face to face. Each country conducted an initial thematic analysis. Consensus was reached through a face-to-face discussion of all 14 national leads. RESULTS: 340 interviews were completed. Several tasks were described within four potential nursing responsibilities, that came up as the analysis themes, being: 1) monitoring therapeutic/adverse effects of medicines, 2) monitoring medicines adherence, 3) decision making on medicines, including prescribing 4) providing patient education/information. Nurses' autonomy varied across Europe, from none to limited to a few tasks and emergencies to a broad range of tasks and responsibilities. Intended level of autonomy depended on medicine types and level of education. Some changes are needed before nursing roles can be optimised and implemented in practice. Lack of time, shortage of nurses, absence of legal frameworks and limited education and knowledge are main threats to European nurses actualising their ideal role in PC. CONCLUSIONS: European nurses have an active role in PC. Respondents reported positive impacts on care quality and patient outcomes when nurses assumed PC responsibilities. Healthcare professionals expect nurses to report observations and assessments. This key patient information should be shared and addressed by the interprofessional team. The study evidences the need of a unique and consensus-based PC framework across Europe.
Keywords: Hospitals; Patient Compliance; Male; Health Knowledge, Attitudes, Practice; Europe; Adult; Aged; dospělí; mužské pohlaví; senioři; Pharmacists; Nurses; průzkumy a dotazníky; kvalitativní výzkum; Evropa; adherence pacienta; Nurse's Role; lidé; ženské pohlaví; farmaceutické služby; zdraví - znalosti, postoje, praxe; Humans; Physicians; lékaři; zdravotní sestry; Qualitative Research; role ošetřovatelky; Female; Surveys and Questionnaires; nemocnice; lidé středního věku; farmaceuti; Pharmaceutical Services; Middle Aged